The impact of teamwork on organizational commitment among information technology employees - Jihmie Macredes Adi Jihek (2008)
Teamwork. is important in any organization, regardless of the field or industry the organization involves. The outcome of teamwork would or will result a successful or positive outcome for the organization. Thus it can influence organizational commitment among employees. The general objective of this research is to determine whether teamwork can affect or influence organizational commitment along with two moderating factors, which are age of company and organizational size. The target sample for this study is Information Technology employees. A total of 150 questionnaires were distributed in six organizations. The organizations are Yayasan Sabah, Petronas, Kota Kinabalu Industrial Park Communication (KKIPC), Telekom Malaysia (TM), Jabatan Perkhidmatan Komputer Negeri Sabah (JPKNS) and Sabah Credit Corporation. However, only 132 questionnaires were successfully collected. SPSS program was used to analyze 12 hypotheses that were constructed. The result of this studies that teamwork and organizational commitment has a significant relationship. Toe moderators on the other hand, do not play a significant role as a moderator but age of company does moderate the relationship between teamwork and affective commitment.